Basic researchEnhanced proliferation and differentiation of osteoblasts induced by co-culturing with Schwann cells - Yuan, Quan; Gong, Ping; Li, Xiaoyu; Wei, Na; Tan, Zhen; Liao, Dapeng; Yang, Xingmei (Archives of Medical Science, 2008)
Introduction: Transplanting Schwann cells into implant sockets might be an effective method to promote sensory responses of osseointegrated implants as a result of the well-known properties of Schwann cells in nerve regeneration. However, it is still unclear whether or not Schwann cells would disturb the osteogenic function of osteoblasts. Material and methods: Using Transwell inserts, osteoblasts derived from neonatal rat calvariae were co-cultured with Schwann cells, and assessed via methylthiazol tetrazolium (MTT) colorimetric assay, Alizarin red staining, alkaline phosphatase (ALP) measurement and osteocalcin (OCN) quantification. The expression of osteogenic marker genes ALP, OCN, and collagen type I (COL-1) was evaluated by quantitative real time polymerase chain reaction (PCR) on day 3, 6 and 9. Results: Compared with the control, there was a significant increase in the proliferation of co-cultured osteoblasts on day 3 and 6 (P<0.05), whereas no difference was shown on day 9. Co-culture of these two types of cells also led to a significant increase in ALP activity and OCN secretion on day 6 and 9. An elevated number of calcified nodules was observed on day 21. In addition, gene expression of ALP, OCN and COL-1 was highly upregulated by Schwann cells. Conclusions: These findings demonstrated that the proliferation and differentiation of osteoblasts could be enhanced by co-culturing with Schwann cells.